The Use of Integra Dermal Regeneration Templates and Cortical Bone Fenestrations over Exposed Tibia. Issue 2 (February 2021) - Hughes, Liam P.; Forman, Steven; Krieg, James C.; Hughes, William B.
Abstract : Summary: We present the case of an 86-year-old woman who suffered full-thickness soft tissue loss secondary to degloving injury to the lower left limb, resulting in an exposed tibia. This patient underwent drilling to create artificial fenestrations in the cortical bone followed by placement of Integra dermal regeneration template. The technique of drilling fenestrations to expose underlying vasculature of cortical bone has not previously been described in its relationship with Integra dermal regeneration templates in large degloving injuries of the lower limb. This technique enabled us to perform earlier skin grafting and ultimately resulted in complete and timely wound closure. We present this case as a comparable alternative treatment in cases of reconstructive surgery secondary to severe burns or trauma to reduce the time required for successful wound closure over exposed bone in full-thickness tissue loss injuries of the lower limb.